2020
DOI: 10.1177/0963689720927392
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Liraglutide Administration Induces Pancreas Neogenesis in Adult T2DM Mice

Abstract: In vivo beta-cell neogenesis may be one way to treat diabetes. We aimed to investigate the effect of glucagon-like peptide-1 (GLP-1) on beta-cell neogenesis in type 2 diabetes mellitus (T2DM). Male C57BL/6J mice, 6 wk old, were randomly divided into three groups: Control, T2DM, and T2DM + Lira. T2DM was induced using high-fat diet and intraperitoneal injection of streptozotocin (40 mg/kg/d for 3 d). At 8 wk after streptozotocin injection, T2DM + Lira group was injected intraperitoneally with GLP-1 analog lirag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In this study, we replicated a T2DM mouse model using a high-fat diet combined with a small amount of multiple injections of STZ ( Deng et al, 2020 ). At 2 months of illness, the fasting blood glucose levels of diabetic mice were significantly higher than those of controls.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we replicated a T2DM mouse model using a high-fat diet combined with a small amount of multiple injections of STZ ( Deng et al, 2020 ). At 2 months of illness, the fasting blood glucose levels of diabetic mice were significantly higher than those of controls.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we revealed the protective efficacy of CIAPIN1 protein against T2DM for the first time using Tat-CIAPIN1 protein. Recently, it has been reported that the hallmark of T2DM is the reduction and loss of islet β-cells [ 54 , 55 ] and a licochalcone can effectively reduce blood glucose and alleviate the phenomenon of weight loss in T2DM mice using HFD combined with STZ [ 52 ]. In addition, several reports have shown protective effects against T2DM animal model as well as diabetic complications [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, YQ treatment also significantly increased the body weight and decreased the consumption of food and water of diabetic rats. Progressive decline of islet ß-cell function and partial loss of islet ß-cell mass were the pathological features of type 2 diabetes [21][22][23]. Pathological analysis showed that the islet ß-cells were atrophic and were distributed unevenly, and local nuclear effects were necrosis and lysis in model group, which were obviously improved by YQ treatment.…”
Section: Discussionmentioning
confidence: 99%